2006
DOI: 10.1080/15022250600560604
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and Sámi Identity – An Analysis of the Tourism‐Identity Nexus in a Sámi Community

Abstract: This article is a study of the tourism-identity nexus in a Sámi community called Karasjohka, often regarded as the Sámi capital in Norway. The aim is, based on focus group interviews, to look at the importance of tourism as a parameter for identity negotiations. The study indicates the existence of a strong Sámi ethos, but people have multiple roles and in many of these the Sáminess is of minor importance. The relation to tourists or to tourism as such seems to be handled through non-Sámi roles. The study unve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 36 publications
0
18
1
Order By: Relevance
“…Such articles show that the Sámi identity is constructed by both the dominant Swedish society and the Sámi themselves. This echoes other researchers' findings, that there is "discursive awareness" of the significance of tourism in its role in constructing Sáminess (Viken, 2006), and that tourism can be used by Sámi individuals to achieve their own subjective goals (Keskitalo & Schilar, 2016;Niskala & Ridanpää, 2016). On the other hand, it contrasts what Pietikäinen (2003) observes about the representation of the Sámi in the national Finnish newspaper Helsingin Sanomat as a primitive and homogenous group.…”
Section: Tourism As the Better Alternative?contrasting
confidence: 52%
See 1 more Smart Citation
“…Such articles show that the Sámi identity is constructed by both the dominant Swedish society and the Sámi themselves. This echoes other researchers' findings, that there is "discursive awareness" of the significance of tourism in its role in constructing Sáminess (Viken, 2006), and that tourism can be used by Sámi individuals to achieve their own subjective goals (Keskitalo & Schilar, 2016;Niskala & Ridanpää, 2016). On the other hand, it contrasts what Pietikäinen (2003) observes about the representation of the Sámi in the national Finnish newspaper Helsingin Sanomat as a primitive and homogenous group.…”
Section: Tourism As the Better Alternative?contrasting
confidence: 52%
“…The "Sáminess" in tourism How "Sáminess" is represented, constructed and utilized in tourism has been examined in previous studies (Niskala & Ridanpää, 2016;Viken, 2006). Through the articles here, it is also shown that as a consequence of the ethno-political discourses on Sápmi and the Sámi, Sáminess is constructed and negotiated through tourism.…”
Section: Tourism As the Better Alternative?mentioning
confidence: 96%
“…In particular, tourism and handicrafts are seen as vital supplementary revenue for Sámi who continue to practise more traditional occupations, such as traditional reindeer herding, fishing, etc., or who currently practise these activities only to some extent (Müller and Pettersson 2001;Scheffy 2004;Dana and Remes 2005;Viken 2006;Leu and Müller 2016;Niskala and Ridanpää 2016). In contrast to indigenous people elsewhere, Sámi engagement in tourism can thus not be seen as a "last option", but represents rather one alternative among others (Viken and Müller 2017).…”
Section: Handicrafts Sáminess and The Duodji Labelmentioning
confidence: 99%
“…Similarly, it seems that past norms were thought to imply that "a Sámi" could not be, e.g. "a Swede", whilst today with Sámi relations, one can choose or switch between identities or adhere fully to both Sámi and Swedish/Norwegian/Finnish identity (Viken 2006). Hence, Sáminess is seen as valuable, a sort of extra-identity and a matter of "who has it":…”
Section: Attractive Sáminessmentioning
confidence: 99%
See 1 more Smart Citation